Ag(I) decorated isomeric triazine complexes as efficient hydrogen storage materials - A theoretical investigation - Abhishek Bag; Gobinda Chandra De; Shampa Bhattacharyya; Bikash Bepari; Himadri Sekhar Das; Sateesh Bandaru; Gourisankar Roymahapatra (Chemistry of Inorganic Materials)
The hydrogen economy has become increasingly important in the global fuel landscape due to the rapid depletion of fossil fuels. Many transition metal-based metal-organic frameworks have been explored for hydrogen (H₂) storage, but finding an optimal solution remains challenging. This study employs Density Functional Theory (DFT) with various functionals and basis sets to examine Ag(I)-decorated isomeric triazines (123, 124, and 135 ​N-positions) as potential H₂ storage materials. We thoroughly investigate the effects of temperature, adsorption energy, and gravimetric capacity for these systems. The simulation results reveal that the isomeric triazine systems, when decorated with metal and loaded with H₂, exhibit gravimetric weight percentages between 5.08 ​wt% and 6.39 ​wt%. Analysis of average adsorption energy, Gibbs free energy change, and other DFT parameters indicates that H₂ molecules are effectively adsorbed on these systems. This research provides valuable insights for the development of stable and high-capacity H₂ storage solutions.